BIODESULFURISASI MINYAK SOLAR PRODUK KILANG PPSDM MIGAS CEPU MENGGUNAKAN BAKTERI Rhodococcus erythropolis - Alchibalt Bima Putra Dzufakar (Swara Patra, 2023)
Diesel oil is a type of fuel for diesel engines as a result of processing from crude oil. One of the content of diesel oil that causes various problems is sulfur compounds. Excess sulfur content will cause odors in processed products, the calorific value produced can decrease, causing corrosive properties in processing equipment at the PPSDM Migas refinery such as fractionation columns, refinery storage tanks, distribution pipes, pumps, and vehicle storage tanks. The limit of sulfur content in diesel oil set by the Director General of Oil and Gas is 50 ppm. This study aims to determine the ability of Rhodococcus erythropolis bacteria to biodesulfurize diesel oil, to determine the growth activity of Rhodococcus erythropolis bacteria to biodesulfurize diesel oil, and to determine whether the biodesulfurization process can cause corrosivity in diesel oil. The method used is biodesulfurization of growing cells using Rhodococcus erythropolis bacteria, sulfur testing is done by ASTM D2622 method, and corrosivity testing is done by ASTM D130 method. The treatments used in this study were variations in the pH of the growth medium, variations in the concentration of diesel oil, and variations in the length of incubation time. In this study, the bacteria Rhodococcus erythropolis succeeded in reducing the highest sulfur content in diesel oil from 2167.9 to 1766.1 (ppm) with pH 8 treatment. The biodesulfurization process caused a decrease in the pH of the media from 8.2 to 7.1 with pH treatment. 8.